Measuring the societal impact of open science – Presentation of a research project - Kim Holmberg; Fereshteh Didegah; Sarah Bowman; Timothy D Bowman; Terttu Kortelainen (Informaatiotutkimuksen yhdistys, 2022)
Research assessment has become increasingly important—especially in these economically challenging times—as funders of research try to identify researchers, research groups, and universities that are most deserving of the limited funds. The goal of any research assessment is to discover research that is of the highest quality and therefore more deserving of funding. As quality is very difficult and time-consuming to assess and can be highly subjective, other approaches have been preferred for assessment purposes (especially when assessing big data). Research assessments usually focus on evaluating the level of impact a research product has made; impact is therefore used as a proxy for quality. Impact can, however, be difficult to identify, track, and quantify, and as the current methods to assess research impact are being increasingly criticized, new methods and data sources need to be investigated. For this purpose, the altmetrics movement is investigating what the online mentions of research products can disclose about the impact research has had and who has been influenced by research. The focus of the research project presented here will be to examine online mentions of research products and to develop methods and tools to evaluate the potential of these mentions for measuring societal impact of Finnish research in Finland and beyond. This research will 1) map the current state of research in Finland using altmetric research methods and data, and 2) investigate novel quantitative indicators of research impact to incentivize researchers in adopting the open science movement.